A comprehensive review on microbial fuel cell technologies: Processes, utilization, and advanced developments in electrodes and membranes. (1st June 2019) - Palanisamy, Gowthami; Jung, Ho-Young; Sadhasivam, T.; Kurkuri, Mahaveer D.; Kim, Sang Chai; Roh, Sung-Hee
Abstract: Microbial fuel cells have gained great interest as an alternative energy conversion system for generating bioenergy. As a bioelectrochemical hybrid system, microbial fuel cells involved in electricity generation and wastewater treatment including nutrients recovery with tremendous benefits such as energy saving, reduced sludge generation and energy conversion. In this review, we mainly emphasize the developments and advancements of electrode and membrane materials for increasing the microbial fuel cell performances in recent years. We reviewed and discussed the different categories of electrode (anode and cathode) materials with various structural, dimensional, compositions and integrations. Moreover, it encloses the cost-effective, biocompatible and highly stable electrode materials with improved microbial fuel cell performance. Using hetero-atom doped 3-Dimensional porous carbon with ultra-fine metal nanoparticles, a large surface area of the electrode material with different dimensional, and new core@shell structure can considerably enhance the oxygen reduction reaction performance during the microbial fuel cell operation. Following this overview, development in membrane materials such as perfluorinated polymer, hydrocarbon polymer, organic-organic hybrid polymer, organic-inorganic hybrid composite, ceramics, and biopolymer membranes are explained in detail. Based on the physical, chemical, mechanical and biocompatible properties, the hybrid composite biopolymer membrane with organic and inorganic additives are recommended as a suitable membrane candidate for increasing the ion conductivity and rectifying the biofouling issues during the long term operation. Finally, the future viewpoints in the microbial fuel cell for effective wastewater treatment process with electricity generation are suggested through various aspects and strategies to afford clean energy and environment. Highlights: Detail information about the advantages, applications and challenges of MFC system. A comprehensive review of microorganism, electrodes and membranes in MFC. Prospective suggestions for the advanced developments of MFC performance. Novel structured, composite and low-cost electrode materials are suggested. Biofouling issues and oxygen cross-over can be controlled by hybrid membranes.